Hubungan Gaya Kepemimpinn Transformasional dengan Kinerja Karyawan - Setyaningrum, Ayu Surti; , Achmad Dwityanto, S. Psi, M.Si (2015)
This study aims to determine the relationship of transformational leadership style with employee performance. The approach used in this study is the quantitative approach. Population in this research is the production employees Surya Abadi Furniture and subjects in this study of 100 people. The data collection method using a scale of transformational leadership style and documentation of employee performance which has been determined from the company. Then to analyze the data in this study using the Pearson product moment correlation of applications with the help of SPSS 15 for Windows. The results showed no significant positive relationship between transformational leadership style with employee performance, where the value of the correlation coefficient (r) of 0.469 with Sig. 0.000 (p <0.01). note that the variables of transformational leadership style has the empirical mean (RE) of 132.57 and the mean hypothetical (RH) of 125 with the medium category, while the variable performance of employees have empirical mean (RE) at 36.68 with the high category. Effective contribution to the transformational leadership style variable of employee performance determinant R squared coefficient (R2) of (22.0%), 88.0% so there are other factors that affect the performance of the employe.